Inhibition of anti-tumour reactivity of immune cells in the salivary gland cancer: A proteomic approach - Rajdeep Chakraborty; Charbel Darido; Aidan Tay; Thiri Zaw; Shoba Ranganathan; Fei Liu; Giuseppe Palmisano (Oral Oncology Reports)
Background: Adenoid cystic carcinoma (ACC), mucoepidermoid carcinoma (MEC), and oral squamous cell carcinoma (OSCC) respond differently to immunotherapy. Pembrolizumab, an immune checkpoint inhibitor, has been approved by the Food and Drug Administration for the treatment of squamous cell carcinomas of the head and neck region. While MEC has shown some response to pembrolizumab; however, ACC is the least responsive. At the molecular level, head and neck cancers produce immunosuppressive molecules, resulting in immune evasion. Therefore, we hypothesised that salivary gland cancer cells produce a higher number of immunosuppressive proteins that cause suppression of the immune system's anti-tumour reactivity. Method: To determine differential protein expressions in OSCC, MEC, and ACC, we constructed cancer–immune cell co-culture models using different oral and salivary gland cancer cells. We performed SWATH, proteome profilers, gene ontology biological function, functional annotation clustering and protein interaction network analysis of all cancer samples in the co-culture models. Results: Analysis of the acquired data showed that the overexpressed proteins in the OSCC cells and participated more in metabolic process, while in the salivary gland cancer cells, overexpressed proteins participated more in immune processes, immune checkpoint pathway. Upon protein function analysis of salivary gland cells, the overexpressed proteins found negatively affecting immune process and checkpoint pathway proteins. Conclusion: Overall, we conclude that salivary gland cancer is less responsive to immunotherapy, possibly because of the high presence of immunosuppressive proteins. However, further analysis is needed to verify the biological functions and interactive partners of each differentially expressed protein in ACC cells.